Volatilitas Harga Ekspor Komoditas Perkebunan Utama Indonesia Tahun 2015-2024 - Khairad, Merdian; Khairad, Fastabiqul (Mahesa Research Institute, 2026)
Plantation commodities constitute an important sector in the Indonesian economy, contributing significantly to foreign exchange earnings through export activities. However, the prices of plantation commodities in international markets tend to fluctuate, which may affect trade stability and income generated from this sector. This study aims to analyze the export price volatility of Indonesia’s major plantation commodities, including crude palm oil (CPO), cocoa, coffee, and rubber, over the period 2015–2024. The study employs secondary data in the form of annual export prices, which are analyzed using a quantitative descriptive approach. Price volatility is measured using the standard deviation of annual price changes to determine the degree of price fluctuations for each commodity. The results indicate that export prices of the four commodities exhibit varying levels of fluctuation during the study period. Cocoa shows the highest level of price volatility, indicating that it experienced the most significant price fluctuations. In contrast, rubber exhibits the lowest level of volatility, suggesting relatively more stable prices, while CPO and coffee demonstrate moderate levels of volatility. These findings provide insights into the stability of export prices of Indonesian plantation commodities and may serve as a basis for policymakers and market participants in formulating price risk management strategies and trade policies in the plantation sector.